The Study of Ancient and Medieval Military History: Benefits for professional military education - Rogers, Clifford J. (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2019)
There is broad agreement that the study of military history is an essential component of professional education for military officers. Although many successful modern commanders, including Napoleon and MacArthur, advocated extending their reading back to ancient times, Clausewitz wrote: “The further back one goes, the less useful mil- itary history becomes.” This essay argues, to the contrary, that officers have much to gain by including pre-modern warfare in their studies. A larger and more diverse data-set of examples and case studies allows for more reliable generalization, gives more opportunities for inspiration, and helps guard against the tempting but unwise assumptions that the next war will be similar to the last one, and the equally tempting and equally unwise presumption that material strength alone will ensure vic- tory. Moreover, historians of ancient and medieval warfare, like officers exercising their core professional responsibility in combat, must grapple with scanty and conflicting evidence. Pre-modern history, like war, is a realm of uncertainty; many of the “facts” can only be known as proba- bilities. The best preparation for seeing through the fog of war, therefore, may be the exercise of peering through the mists of time.